Narratives of the worst experiences associated with peritraumatic distress during the COVID-19 pandemic: a mixed method study in the USA and Italy. Issue 2 (19th December 2022) - Cipolletta, Sabrina; Tomaino, Silvia Caterina Maria; Rivest-Beauregard, Marjolaine; Sapkota, Ram P.; Brunet, Alain; Winter, David
ABSTRACT: Background: Although symptoms of posttraumatic stress disorder (PTSD) have been associated with the COVID-19 pandemic experiences, no study has explored yet the association of specific COVID-19 narratives with peritraumatic distress, the precursor of PTSD. Objective: To explore the worst experiences associated with peritraumatic distress during the first wave of the COVID-19 pandemic. Method: Adult residents ( N = 1098), from the US ( n = 741) and Italy ( n = 357), completed an online survey including socio-demographic data, COVID-19-related experiences, the Peritraumatic Distress Inventory and an open question on their worst experiences during the first period of the COVID-19 pandemic (April–May 2020). A thematic content analysis (TCA) was conducted on the answers to the open question and a classification and regression tree (CART) analysis was used to identify the themes that best predicted the clinical levels of peritraumatic distress. Results: The main TCA themes related to participants' worst COVID-19 experiences were anxiety, threat, loss, anger, stress and constriction. Threat was the most prevalent theme and correlated with experiences such as being quarantined, being infected and a loved one receiving the diagnosis. US participants' descriptions of their worst experiences related more to life-threat and loss, while Italians reported more threat to the world, stress, social isolation, and feeling trapped. In the CART analysis, the main predictor (79.9%) was perceiving negative effects from the COVID-19 crisis. Among them, a COVID-related threat to self-experience was the most robust predictor. In its absence, being deprived of resources or experiencing high levels of anxiety were other robust predictors. Conclusions: The study provided evidence of the utility of a mixed-method approach in conceptualizing experiences associated with the COVID-19 pandemic and the risk of traumatic symptoms. Its findings may inform healthcare interventions and policies for tackling the new challenges posed by the COVID-19 pandemic. HIGHLIGHTS Clinically significant levels of peritraumatic distress symptoms were prevalent during the COVID-19 pandemic. Clinically significant levels of peritraumatic distress during the COVID-19 pandemic were related to experiences of life-threat, resource deprivation, and anxiety, cross-cutting the themes articulated by the thematic content analysis of anxiety, threat, loss, anger, stress and constriction. The US and Italian participants' descriptions of their worst experiences differed in subtle but important ways, with Americans reporting more life-threat and losses compared to Italians reporting more threat to the world, stress, social isolation, and feelings of being trapped.